SOCIOPRENEUR SEBAGAI STRATEGI PENINGKATAN PEMBERDAYAAN MASYARAKAT DALAM UPAYA PENCEGAHAN STUNTING - Bartini, Istri; Era Revika; Fitriani Mediastuti; Rawi Miharti; Eni Kartika Sari (P3M Universitas Aisyiyah Surakarta, 2025)
Background: The prevalence of stunting in Indonesia is still high and the reduction has not met the target. Timbulharjo Village, Sewon Bantul Yogyakarta is one of the special locations (locus) for handling stunting. Community education and empowerment are still needed to reduce stunting in this village. The sociopreneur approach is one of the innovative strategies to increase community participation and motivation in preventing stunting. Objective: Increasing community empowerment in stunting prevention efforts from upstream to downstream through a sociopreneur approach. Method of Application of Science and Technology: Activities of students across study programmes of STIKes Akbidyo in the form of sociopreneur projects for community empowerment in stunting prevention. The project was carried out on 4 target groups (adolescents, women, pregnant women & mothers of toddlers, general public) through educational activities and the pioneering of sociopreneur products. Results: In the target adolescents, education was carried out at the youth posyandu with additional aroma therapy production activities, in the target women of reproductive age (WUS), pregnant women and mothers of toddlers conducted education about nutrition and production of food products from moringa leaves, while in the target group of the general public conducted education through mural media and production of moringa tempeh nuggets. Conclusion and lesson learned: Sociopreneur is an effective strategy in increasing community motivation to pay more attention to stunting prevention efforts. There is a need for continuous mentoring of business start-ups based on social goals (sociopreneur). Keywords: sociopreneur, stunting, community empowerment